Study on Value Assessment of the Old Town of Xanakharm for Rehabilitation toward Integration to Local and Regional Tourism Routes - SENGONKEO, Luangphasy; KHAMMOUNGKHOUN, Anousa; CHNATHANKHONE, Kalouna; SOUTHICHACK, Phonesavanh; ONMAVONG, Thanouphet (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This study aims to assess the value of the old town of Xanakharm for its potential restoration as a tourist destination connected to local and regional tourism routes. The research employed documentary analysis, field surveys, and questionnaires using a descriptive-analytical approach. Findings indicate that Xanakharm possesses a rich historical heritage, particularly related to Buddhism, with 32 ancient temples and notable sites such as Wat Yai Phahot, Phathat Si Phoum, and Wat Saen. Regarding tourism potential, 78% of respondents believe the town has strong appeal, highlighting its historical landmarks and traditional festivals (12%) as key attractions. Tourism development is also seen as a means to create jobs (52%), stimulate the local economy (44%), and preserve cultural heritage (6%). In terms of restoration priorities, Wat Phahot Yai (29.85%) and Wat Dongkangmeuang (29.10%) received the highest levels of interest. Moreover, 50% of respondents emphasized the importance of community participation in conserving customs and traditions. Overall, the old town of Xanakharm holds significant potential to become a historical and cultural tourism destination, particularly in relation to Buddhism and traditional practices. Restoration and integration into broader tourism networks are appropriate, provided there is a strong focus on community involvement, infrastructure development, and effective promotion to ensure long-term sustainability.